Interprofessional education about shared decision making for patients in primary care settings - Col, N.; Bozzuto, L.; Kirkegaard, P.; Loon, M.K.; Majeed, H.; Ng, C.J.; Pacheco-Huergo, V. (2011)
With an increasingly complex array of interventions facing healthcare professionals and patients, coupled with a potentially diverse number of professionals operating within the primary care team, the adoption of shared decision making (SDM) - with or without patients' decision aids - in an interprofessional manner is essential to ensure the highest quality of care for patients. In this article, we propose a framework for interprofessional education about SDM targeted to primary care settings. Five areas of knowledge and skills were agreed to be essential for all relevant stakeholders for interprofessional education in SDM to be successful: understanding the concept of SDM; acquiring relevant communication skills to facilitate SDM; understanding interprofessional sensitivities; understanding the roles of different professions within the relevant primary care group; and acquiring relevant skills to implement SDM. We suggest a series of teaching methods for the aforementioned areas, using principles from adult learning.